Pathology of Silver Rasbora (Rasbora argyrotaenia) after Experi-mentally Infection with Edwardsiella tarda : Edwardsiellosis in Silver Rasbora - Nindi, Inda Arsyi; Febrina, Melinda; Rahmawati, Anggi Rusita; Ulkhaq, Mohammad Faizal; Tjahjaningsih, Wahju; Kusdarwati, Rahayu; Pardede, Maria Agustina; Kumalasari, Ditta Putri; Loh, Jiun-Yan (Journal of Aquaculture and Fish Health, 2025)
The high demand for silver rasbora (Rasbora argyrotaenia) from the wild had led to declining resources, making fish cultivation necessary. One of the challenges in fish farming is diseases caused by bacteria, such as Edwardsiella tarda, which can lead to Edwardsiellosis and result in mass mortality among fish. This study aimed to analyze the pathology of silver rasbora after experimental infection with E. tarda. Four hundred silver rasbora (5.4±7 cm and 0.47±2.63 g) were reared in twenty aquariums. The treatments consisted of four groups with five replicates, including immersion in E. tarda 1011 CFU/ml (P1), 1012 CFU/ml (P2), 1013 CFU/ml (P3), and a negative control (without E. tarda) (P0) for a 14-days rearing period. Parameters observed included survival rate, stress responses (plasma cortisol, blood glucose, and ventilation rate); hematology profile (total erythrocytes, total leukocytes, differential leukocytes, and hemoglobin levels), histopathological alterations in organs, survival rate, and clinical symptoms. The results showed that immersion in E. tarda did not affect fish mortality. However, other parameters, including hematological profile, stress responses, and histopathological alterations, showed increased values and several pathological changes, yet remained within normal limits.